THE POSSIBILITIES OF REDUCING ENERGY CONSUMPTION OF THE ROBOT DRIVES IN THE DESIGN PHASE - I. V. Tarzhanov (Российский технологический журнал)
The article discusses possible ways of designing with reduction of the energy consumption of robots by choice of schedules, the inclusion of actuators degrees of freedom, and reduction of work forces of friction when braking degree of freedom near the axis positioning.